Estratégias e marcadores conversacionais na construção do diálogo em Os novos, de Luiz Vilela - Penedo, Fernanda Pereira (2013)
This study aims to identify markers and conversational strategies used by the characters in the dialogue of fiction. We use excerpts taken from the corpus selected for analysis of dialogue built, the novel The new, the storyteller mining Luiz Vilella. In the work, we highlight the schemes used by the characters in different communicative situations and observe the rich set of examples of typical variations of oral language. The corpus is not a transcript, but replaces the recordings of conversations in natural situations. Constructions of lines of characters created by Vilela, often approaching the reality spoken language of the reader. Vilela transmits information regarding the interaction process for the construction of his dialogues, transforming its texts into excellent source of study of conversation through written texts